2017
DOI: 10.1093/bib/bbx031
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed peptides in high-throughput proteomics data

Abstract: With the advent of high-throughput proteomics, the type and amount of data pose a significant challenge to statistical approaches used to validate current quantitative analysis. Whereas many studies focus on the analysis at the protein level, the analysis of peptide-level data provides insight into changes at the sub-protein level, including splice variants, isoforms and a range of post-translational modifications. Statistical evaluation of liquid chromatography-mass spectrometry/mass spectrometry peptide-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…Quantitative MS identified 2220 phosphopeptides and 4798 phosphorylation sites (Table S1). 225 phosphopeptides (180 proteins, 254 sites) were identified that displayed significant change in abundance upon X‐irradiation of wild‐type lines (Table S2), analyzing four independent replicates for each treatment and correcting for a false discoveries using limma in R (van Ooijen et al ., ). Of the 254 X‐ray responsive phosphorylation sites identified here, only six were previously identified in the DNA damage signalling network of mature wild‐type plants (Table S2), highlighting the wide range of phosphoproteins induced upon genotoxin treatment.…”
Section: Resultsmentioning
confidence: 97%
“…Quantitative MS identified 2220 phosphopeptides and 4798 phosphorylation sites (Table S1). 225 phosphopeptides (180 proteins, 254 sites) were identified that displayed significant change in abundance upon X‐irradiation of wild‐type lines (Table S2), analyzing four independent replicates for each treatment and correcting for a false discoveries using limma in R (van Ooijen et al ., ). Of the 254 X‐ray responsive phosphorylation sites identified here, only six were previously identified in the DNA damage signalling network of mature wild‐type plants (Table S2), highlighting the wide range of phosphoproteins induced upon genotoxin treatment.…”
Section: Resultsmentioning
confidence: 97%
“…Consequently, the proteins that are detected differ from run to run, resulting in missing quantifications in the (replicate values of the) data set. Although these can be imputed, we recently showed that this leads to high levels of false positives and hence, is not recommended for high‐throughput protein analysis . Future proteomics experiments will yield additional proteins involved in Th skewing, but the observation that only a small fraction of all (quantified) proteins are associated with Th differentiation is in line with our genome wide mRNA profiling experiments.…”
mentioning
confidence: 69%
“…The mouse/spleen group from which the cells were derived was used as a co‐variate to control for replicate associated effects, for details see refs. and . The intensity data was processed using custom R scripts: after log 2 ‐transformation, the sample medians were shifted onto a single median value (Figure S3, Supporting Information).…”
mentioning
confidence: 97%
“…For the purpose of variable selection CAMPP employs limma (linear models for microarray data) for differential expression/abundance analysis (DEA, DAA) (Ritchie, et al, 2015). Although limma was originally designed for analysis of microarray data and subsequently revised to handle RNA sequencing data, this software is very flexible and has recently been shown to perform very well with quantitative mass spectrometry data (Kammers, et al, 2015;van Ooijen, et al, 2018). In addition to being versatile, limma has been shown to work exceptionally well on datasets with small sample sizes (Seyednasrollah, et al, 2015;Soneson and Delorenzi, 2013).…”
Section: Variable Selection With Differential Expression Analysis Andmentioning
confidence: 99%